2012
DOI: 10.1155/2012/843025
|View full text |Cite
|
Sign up to set email alerts
|

Gelam (Melaleucaspp.) Honey-Based Hydrogel as Burn Wound Dressing

Abstract: A novel cross-linked honey hydrogel dressing was developed by incorporating Malaysian honey into hydrogel dressing formulation, cross-linked and sterilized using electron beam irradiation (25 kGy). In this study, the physical properties of the prepared honey hydrogel and its wound healing efficacy on deep partial thickness burn wounds in rats were assessed. Skin samples were taken at 7, 14, 21, and 28 days after burn for histopathological and molecular evaluations. Application of honey hydrogel dressings signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…Wound contraction was calculated at the 3 rd , 5 th , 10 th and 15 th days after wound induction. The percentage of wound healing was calculated as performed by [ 8 , 40 ]: Progressive decrease in wound area was measured periodically by tracing the wound margin on a tracing paper. The tracing was then placed onto 1 mm² graph sheet paper and the numbers of squares were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Wound contraction was calculated at the 3 rd , 5 th , 10 th and 15 th days after wound induction. The percentage of wound healing was calculated as performed by [ 8 , 40 ]: Progressive decrease in wound area was measured periodically by tracing the wound margin on a tracing paper. The tracing was then placed onto 1 mm² graph sheet paper and the numbers of squares were counted.…”
Section: Methodsmentioning
confidence: 99%
“…Honey has been used in folk medicine since ancient times and has more recently been rediscovered by medical researchers for its use in dressing acute and chronic wounds. Traditionally, honey has been used to treat burns, infected and non-healing wounds and ulcers, boils, pilonidal sinus, venous and diabetic foot ulcers (1-6). Recent studies confirm the efficacy of honey in treating venous ulcers (7).…”
Section: Contextmentioning
confidence: 99%
“…Based on the histopathological evidence, it showed that honey hydrogel significantly attenuated inflammatory response (p < 0.05) on seventh day of treatment and modulated the proinflammatory cytokines involve in wound healing at molecular level. This study has clearly demonstrated the potential effectiveness of honey hydrogel dressing in accelerating the burn wound healing through the various effects on cellular elements and cytokines involved (Mohd Zohdi et al 2012). …”
Section: Accelerate Wound Healing Properties Of Ghmentioning
confidence: 75%
“…In addition, a group a researchers worked on the wound healing properties of GH and developed the idea of honey hydrogel dressing for the management of wound healing (Mohd Zohdi et al 2012). It was found out that application of honey hydrogel dressing significantly increased (p < 0.05) wound closure rate and the rate of re-pithelialization compared to control hydrogel and OpSite film dressing.…”
Section: Accelerate Wound Healing Properties Of Ghmentioning
confidence: 99%